New Guideline for Chronic Kidney Disease 2024, What Primary Care Can Do About It?: A Narrative Review - Simanjuntak, Arya Marganda; Heryadi, Samantha Yaffa; Sembiring, Ligat Pribadi (PERNEFRI (PERHIMPUNAN NEFROLOGI INDONESIA), 2026)
Chronic Kidney Disease (CKD) presents an urgent global public health crisis, affecting over 850 million people worldwide, with low-income nations like Indonesia facing a high burden of undiagnosed cases due to limited awareness and a deficient primary care system. This paper serves as a vital, practical response to the novelty of the KDIGO 2024 Clinical Practice Guideline update, which incorporates a decade of new evidence, including the ethical imperative to eliminate the race coefficient from eGFR equations and the introduction of consensus-based